Year-End Fundraising: Where to Invest Your Time - Barden, Pamela (NonProfit Pro (Online), 2015)
[...]our jobs are to benefit from that spirit of generosity (or a desire for a tax deduction, depending on your level of cynicism) as much as possible. Have a “courtship” strategy this year-end that acknowledges that the first gift doesn’t directly lead to absolute commitment. 5. Retail outlets aren’t advertising in the hopes that someone will come in and just buy one item; they are glad for that sale, but their successes are dependent on repeat customers. (Oh, that it were as easy as following a recipe.) There are plenty of things on which to focus—Giving Tuesday, maximizing our Google AdWords, using “power” words in copywriting, having strong subject lines, telling stories, having a website optimized for mobile, and on and on.